A STUDY ON YOUTH’S PREFERENCE FOR KHADI APPARELS -THE SIGNATURE AND SUSTAINABLE FABRIC OF INDIA (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
Khadi- the original fabric of India is alternatively  termed as “Khaddar”, a hand-spun and hand  woven material, greatly helps to sustain the  rural economy by providing employment to  rural artisans and women. People who wear  Khadi are self-motivated and bore a positive  attitude to buy the fabric as indicated through  the application of Theory of Planned Behaviour  in the study. The contribution of Designers is  immense to attract potential buyers for wearing  Khadi. Despite being the culture and heritage,  Khadi is not worn by the masses. Therefore in  this paper an attempt has been made to find  out the reasons for the non-acceptance of Khadi  and promote it as a fashion fabric through the  survey. Young Celebrity endorsement, Online  Sales, promoting exports, Production research  for quality improvement and round-the-year  discount seasons have been suggested to make  Khadi a long-lived sustainable fabric.
Keywords: Apparels; Consumer Behaviour; Khadi; Theory of Planned Behaviour; Sustainable